2005
DOI: 10.1105/tpc.104.029975
|View full text |Cite
|
Sign up to set email alerts
|

ARABIDOPSIS CRINKLY4 Function, Internalization, and Turnover Are Dependent on the Extracellular Crinkly Repeat Domain

Abstract: The study of the regulation and cellular dynamics of receptor kinase signaling in plants is a rapidly evolving field that promises to give enormous insights into the molecular control of signal perception. In this study, we have analyzed the behavior of the L1-specific receptor kinase ARABIDOPSIS CRINKLY4 (ACR4) from Arabidopsis thaliana in planta and have shown it to be present in two distinct compartments within cells. These represent protein export bodies and a population of internalized vesicles. In parall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
108
3

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(125 citation statements)
references
References 64 publications
(92 reference statements)
13
108
3
Order By: Relevance
“…One possible mechanism for this is that positive signaling for aleurone cell fate specification occurs by membrane proteins that are ubiquitously distributed, but only active (uninhibited) in surface membranes of endosperm surface cells. Although the molecules responsible for the proposed signaling are yet to be identified, Cr4 and Dek1 are attractive candidates, both proteins being predicted to be located in plasma membranes and both having extracellular domains capable of mediating cell-to-cell interactions (Becraft et al, 1996;Lid et al, 2002;Gifford et al, 2005). Additional observations that make Dek1 an attractive candidate for a direct role in aleurone cell fate specification is that it acts cell autonomously; starchy endosperm cells that lack Dek1 are unable to respond to surface position by converting to the aleurone cell fate (Becraft and Asuncion-Crabb, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible mechanism for this is that positive signaling for aleurone cell fate specification occurs by membrane proteins that are ubiquitously distributed, but only active (uninhibited) in surface membranes of endosperm surface cells. Although the molecules responsible for the proposed signaling are yet to be identified, Cr4 and Dek1 are attractive candidates, both proteins being predicted to be located in plasma membranes and both having extracellular domains capable of mediating cell-to-cell interactions (Becraft et al, 1996;Lid et al, 2002;Gifford et al, 2005). Additional observations that make Dek1 an attractive candidate for a direct role in aleurone cell fate specification is that it acts cell autonomously; starchy endosperm cells that lack Dek1 are unable to respond to surface position by converting to the aleurone cell fate (Becraft and Asuncion-Crabb, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Cr4 and Dek1 have also been implicated in epidermal cell fate specification in different organs of Arabidopsis (Arabidopsis thaliana) and tobacco (Nicotiana tabacum; Johnson and Russell, 1982;Tanaka et al, 2002;Gifford et al, 2003Gifford et al, , 2005Ahn et al, 2004;Cao et al, 2005;Lid et al, 2005). It therefore appears likely that epidermal cell fate specification in plants, including aleurone cells, occurs through a process that is conserved among all organs and between monocots and dicots.…”
mentioning
confidence: 99%
“…However, attempts to demonstrate an influence of cytokinin or the inhibitor of endosomal recycling brefeldin A on the localization of cytokinin receptor-GFP fusion proteins have not been successful so far (Wulfetange, 2010). Thus, a model involving the recycling of the receptors between the ER and the PM, as has been described for BRI1 and the receptor-like kinase CRINKLY4 (Gifford et al, 2005;Geldner et al, 2007), is currently not supported experimentally for the cytokinin receptors.…”
Section: A Modified Model For Cytokinin Signalingmentioning
confidence: 99%
“…This has been indirectly established for the tomato (Lycopersicon esculentum) LeEiX2 receptor of the fungal ethylene-inducing xylanase elicitor, which contains a Tyr-based motif functioning as an endocytotic signal (Ron and Avni, 2004). Moreover, some receptor-like kinases are localized in an FM4-64 positive compartment (Gifford et al, 2005), sometimes complexed with their ligand (Shah et al, 2002;Russinova et al, 2004), although these receptors undergo constitutive internalization. The cryptogein receptor has not been identified yet, but preliminary observations of colloidal gold-labeled cryptogein inside BY-2 cells 5 min after elicitor treatment suggest that the cryptogein receptor follows a similar route (J. Lherminier, unpublished data).…”
Section: Pharmacological Interference Supports a Role For Rme In Crypmentioning
confidence: 99%
“…However, plasma membrane receptor-ligand interactions are frequently incompletely characterized. The involvement of endocytotic processes of receptors for signal transduction during plant development has been discovered only recently (Shah et al, 2002;Russinova et al, 2004;Gifford et al, 2005;Kwaaitaal et al, 2005). Shah et al (2002) suggested that only cells showing endocytosis of the receptors are actively engaged in ligand-mediated signaling.…”
mentioning
confidence: 99%